"We Are Not Criminals": Sex Work Clients in Canada and the Constitution of Risk Knowledge. Issue 3 (25th June 2018) - Sterling, Andrea; van der Meulen, Emily
Abstract: While Canada has long criminalized aspects of sex work, the specific act of purchasing sexual services was not against the law per se. In 2014, however, the then Conservative government implemented new legislation targeting sex work clients. Given the criminalization and persistent stigmatization of their activities, assessing clients' changing actions, perceptions, and knowledge of the new legislation is challenging. We thus turned to a major Canadian online sex work review forum to examine postings on forum threads. This paper examines the risk knowledge practices in which clients engage as they try to make sense of the modified legal regime and avoid new legal risks. Our findings illuminate clients' varied understandings of their own criminalization. Résumé: Au Canada, bien que plusieurs aspects entourant le travail du sexe aient longtemps été criminalisés, l'action spécifique d'acheter des services sexuels ne constituait pas, en soi, une violation à la loi. En 2014, le gouvernement Conservateur de l'époque a toutefois ratifié une nouvelle législation ciblant les clients des travailleurs du sexe. Compte tenu de cette criminalisation et de la stigmatisation persistante de leurs activités, il demeure difficile d'évaluer les actions, les perceptions et les connaissances changeantes desdits clients en ce qui a trait à la nouvelle législation. Nous nous sommes donc tournées vers un important forum virtuel canadien d'évaluation du travail du sexe pour examiner les échanges sur le fil de discussion. Cet article examine les pratiques de connaissance des risques utilisées par les clients dans leurs tentatives de donner un sens à la nouvelle législation et d'éviter de nouveaux risques juridiques. Nos résultats illustrent la compréhension variée des clients quant à leur propre criminalisation.